Karakterisasi Katalis Cu-Cr /Kieselguhr - Galuh Widiyarti (Dept. of Chemical Engineering, Diponegoro University, 2001)
Copper-chromite active metal catalyst was prepared by using impregnation method with kieselguhr (Al2O3SiO2) as supporting material. The content of metal active was 20% with 1:1 proportion of complex metal Cu : Cr. The specific surface area of catalyst gave specific surface area of 2,537 m2/ gram. X-ray Diffraction analysis, shown that active metal of Cu-copper Cu and cristobalite SiO2. Temperature program analysis, shown that reduction temperature of catalyst was 300 0Cusing by Scanning Electronic Microscope (SEM), the morphology of catalyst was determined.Keyword : Copper-Chromite catalyst, impregnation, Kieselguhr